First Steps Toward Improving DoD STEM Workforce Diversity - Nelson Lim, Abigail Haddad, Dwayne M. Butler, Kate Giglio (RAND Corporation, 2013)
On August 18, 2011, the President issued Executive Order 13583, â€œEstablishing a Coordinated Government-Wide Initiative to Promote Diversity and Inclusion in the Federal Workforce.â€ The Department of Defense (DoD), in response, soon released an organizational diversity and inclusion strategic plan addressing workforce diversity, workplace inclusion, and force sustainability. In turn, leaders from DoDâ€™s Assistant Secretary of Defense for Research and Engineering (ASD[R&E]) and the Office of Diversity Management and Equal Opportunity (ODMEO) sought to further support the Presidentâ€™s order in ways specific to DoDâ€™s science, technology, engineering, and mathematics (STEM) workforce, and convened a two-day conference, the Summit, on November 1, 2012. Senior executives working on personnel issues within DoD, federal agencies, the private sector, and academia gave presentations and participated in discussions. These presentations focused on issues related to the DoD STEM workforce and its diversity, particularly racial/ethnic and gender diversity. This report supports the efforts of the DoD Diversity STEM Summit by responding to the proceedings in a way that may provide a foundation for further research, analysis, and action. The report describes current diversity policies and demographic trends and provides a template for comparing STEM-diversity outreach programs to support ASD(R&E) and ODMEOâ€™s interest in bringing populations currently underrepresented in STEM into DoDâ€™s STEM workforce mix. The report also offers a number of initial recommendations for DoD leaders to consider as they move forward with their efforts to increase the diversity of the STEM workforce.